5x-3+5-3x=-18

Simple and best practice solution for 5x-3+5-3x=-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3+5-3x=-18 equation:


Simplifying
5x + -3 + 5 + -3x = -18

Reorder the terms:
-3 + 5 + 5x + -3x = -18

Combine like terms: -3 + 5 = 2
2 + 5x + -3x = -18

Combine like terms: 5x + -3x = 2x
2 + 2x = -18

Solving
2 + 2x = -18

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 2x = -18 + -2

Combine like terms: 2 + -2 = 0
0 + 2x = -18 + -2
2x = -18 + -2

Combine like terms: -18 + -2 = -20
2x = -20

Divide each side by '2'.
x = -10

Simplifying
x = -10

See similar equations:

| r+10=16 | | 6n-5n=-6n+3n | | 5x-3x-2=2(x-7) | | x+1/20=4000 | | 6n-5n=-6n+n | | 2x*4-x+7+4x-8-5x^2+2+3x= | | 2/3x-1/3=32/3 | | 2/3x-12=10 | | 30-75=10z-4 | | 9y-7-5y+6=0 | | 6+2(3y-2)=4(1+y) | | d-8=10 | | 4x-x=22-4 | | 12+4q=17+3q | | 51=3+8x | | U=might | | Ak-r=an | | 24/-10-5/-4 | | 3(7+2)=3(7)+3(2) | | 2z^2+9z=5 | | 1.8x+2.8=2.5x+2 | | 4(x+3)-4=8x+10-4 | | 3x+5=4x-6 | | 3.2/3.44 | | 3(x-2)=5x-2x-6 | | m/7=3/5 | | -x-(13+4x)=-3(6-9x)+2 | | w=-10.5+0.5p | | 5m-13m=16 | | 1/3*3.14*4*4*7 | | 9x-2(x-8)=7(x+1)+6 | | 3x-2(x+3)=5x-2x |

Equations solver categories